Ghrelin-induced neuronal NPY promotes brain metastasis in lung cancer patients with low BMI - Abhishek Tyagi; Shih-Ying Wu; Jee-Won Kim; Ravindra Pramod Deshpande; Kerui Wu; Eleanor C. Smith; Giuseppe L. Banna; Kounosuke Watabe (Nature Communications)
Abstract Obesity is a known risk factor for many cancers, yet recent studies reveal a paradoxical association between low body mass index (BMI) and increased brain metastasis in lung cancer—referred to as the “obesity paradox,” with unclear molecular mechanism(s). Here, we show a significantly higher incidence of brain metastasis in low-BMI lung cancer patients compared to those with high-BMI or other cancer brain metastasis in a pan-analysis of 7628 patients. Mechanistically, low BMI activates ghrelin-GHSR signaling, increasing neuronal neuropeptide Y (NPY) secretion, which promotes tumor metabolic reprogramming via NPY-Y5R, facilitating brain colonization. Elevated plasma ghrelin levels in cancer-free low-BMI subjects suggest its potential as a prognostic biomarker for predicting brain metastasis. Notably, targeting NPY-Y5R or reversing low BMI effectively suppresses brain metastasis, supporting its pro-metastatic role. These findings provide a strong rationale for developing targeted interventions to treat or prevent brain metastasis in lung cancer patients with low BMI.